Acute Kidney Injury Following Rhabdomyolysis in Critically Ill Patients - Saverymuthu Alvin (Sciendo, 2021)
Rhabdomyolysis, which resulted from the rapid breakdown of damaged skeletal muscle, potentially leads to acute kidney injury.